A Deg-protease family protein in marine Synechococcus is involved in outer membrane protein organization - Stuart, Rhona K.; Brahamsha, Bianca; Palenik, Brian (Frontiers in Marine Science, 2014)
Deg-family proteases are a periplasm-associated group of proteins that are known to be involved in envelope stress responses and are found in most microorganisms. Orthologous genes SYNW2176 (in strain WH8102) and sync_2523 (strain CC9311) are predicted members of the Deg-protease family and are among the few genes induced by copper stress in both open ocean and coastal marine Synechococcus strains. In contrast to the lack of a phenotype in a similar knockout in Synechocystis PCC6803, a SYNW2176 knockout mutant in strain WH8102 was much more resistant to copper than the wild-type. The mutant also exhibited a significantly altered outer membrane protein composition which may contribute to copper resistance, longer lag phase after transfer, low-level consistent alkaline phosphatase activity, and an inability to induce high alkaline phosphatase activity in response to phosphate stress. This phenotype suggests a protein-quality-control role for SYNW2176, the absence of which leads to a constitutively activated stress response. Deg-protease family proteins in this ecologically important cyanobacterial group thus help to determine outer membrane responses to both nutrients and toxins.